The men who feed the world? Putting masculinities on the agenda for crop breeding research for development - Tarjem, Ida Arff; Tufan, Hale Ann (Frontiers in Sustainable Food Systems, 2023)
Science, technology, engineering, and mathematics (STEM) fields that are dominated by men and masculine have historically been shown to lead to poor representation and discrimination of women and gender diverse scientists, managers, and leaders. This in turn negatively impacts inclusive innovation processes and outcomes. We claim that crop breeding is one such field that is undeniably dominated by men, and even masculine, and could therefore harbor the very same dynamics of exclusion. Yet there is a dearth of research systematically investigating how masculinities are performed in the institutions, organizations, cultures, discourses, and practices of crop breeding. In this Perspective piece, we present a theoretically informed hypothesis of crop breeding organizations as representing spaces where masculinities associated with rurality, management, and science and technology come together in ways that may marginalize women and gender diverse individuals, including in intersection with sexuality, race, ethnicity, and disability. In developing this hypothesis, we draw upon theoretical and empirical insights from masculinity studies in rural sociology, management and organization studies, and feminist technoscience studies. We demonstrate how critical men and masculinities studies can help expose masculinities in crop breeding to investigation, discussion, criticism, and change. As we seek to advance equality in and through crop breeding organizations, this framing helps to guide future research with potential to positively impact the culture of crop breeding research.